ELECTRICAL POWER ANALYSIS OF SINGLE PHASE INDUCTION MOTOR IN PALM SUGAR FLOURING MACHINE - Marlon Tua Pangihutan Sibarani; Penteris Rumissar Panurisma Naibaho; Rufinus Nainggolan; Mhd. Daud Pinem; Joko Sutrisno (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Palm sugar flour machine is a machine used to make flour from palm sugar. Palm sugar flour can be used as a processed food product. Compared to manually grinding palm sugar by hand which requires a lot of energy and time, the palm sugar flour machine can be a solution to facilitate the work in the palm sugar processing industry, both on a small and medium scale and a home industry. With this, the author analyzes the electric power of the induction motor on this palm sugar flour machine to determine the power generated from each experiment carried out and the capacity generated from the palm sugar flour machine. The palm sugar flour machine has dimensions of 600 mm x 300 mm x 800 mm with a 1 HP, 1 phase electric motor power, 220 V voltage and 50 Hz frequency. After conducting the analysis of the calculation of electrical power average of the single-phase induction motor on this palm sugar flour machine is 455.81 W and the thickness of floured palm sugar is 0.1 mm.